Nutrition literacy and salt reduction measures: a mediating role of salt reduction intention - Hu, Xiaoting; Sun, Yuhui; Tian, Xi; Liu, Huaqing (Frontiers in Nutrition, 2025)
BackgroundExcessive salt intake is a public health issue, posing considerable risks to individuals’ health. Various salt reduction strategies are being implemented globally. Nutrition literacy (NL) enables people to make well-informed food decisions that impact their well-being. Individual’s behavior is primarily shaped by their intentions, which, in turn, are influenced by their knowledge and attitudes regarding the action. The current study aims to estimate the relationships between NL and salt reduction measures and examine whether the intention to reduce salt intake mediates these relationships.MethodsThis is a cross-sectional study conducted among adults in Bengbu, China. NL was assessed using a twelve-item short-form NL scale. Salt reduction measures and intention were identified through questionnaires. A binary logistic regression model was applied to calculate the odds ratio (OR) and 95% confidence interval (CI) for this association.ResultsOverall, 50.7% of participants indicated implementing salt reduction measures, with 32.5% indicating a strong intention to do so. NL showed a significant positive association with the salt reduction intention (OR = 1.07, 95% CI: 1.06–1.09) and measures (OR = 1.06, 95% CI:1.04–1.07). This association was particularly evident in checking nutritional labels for sodium content (OR = 1.08, 95% CI: 1.05–1.10), using low-sodium salt (OR = 1.06, 95% CI: 1.04–1.08), and using salt-restriction tools (OR = 1.05, 95% CI: 1.03–1.07). And, the salt reduction intention (mediation effect ratio = 66.7%) mediated the relationship between NL and salt reduction measures.ConclusionNL is positively associated with salt reduction measures, and salt reduction intention partially mediate their associations. These findings underscore the need for NL-targeted interventions or programs that enhance individuals’ intention to adopt salt reduction measures within the Chinese population.